THE INFLUENCE OF WORD OF MOUTH (WOM) AND COMPLETENESS PRODUCTS TO PURCHASE DECISIONS US PHONECELL SUKARAME CASE STUDY - Fattah F, A’lan; Mirandha, Yovie; Fadil, Ahmad; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2022)
Word of Mouth is also known as "mouth-to-mouth marketing" or word-of-mouth communication is a verbal communication between one person and another that can be done face-to-face or through electronic media. Product completeness is an important concept in supply chain management and marketing. Product completeness refers to all elements or features included in a product or service to meet customer needs, expectations, and satisfaction. And consumer purchasing decisions are influenced by various factors, including personal, economic, functional, cultural, and psychological factors. These factors can affect the consumer decision-making process, which includes recognizing a need, finding information, evaluating alternatives, making purchasing decisions, and evaluating the post-purchase experience